SYNTHESIS AND CHARACTERIZATION OF SOME METAL IONS WITH {[5-(4-CHLOROPHENYL)-1,3,4-OXADIAZOL-2-YL]THIO} ACETIC ACID - Yousif, Emad; Rentschler, Eva (Al-Nahrain Journal of Science, 2010)
New metal complexes of the ligand {[5-(4-chlorophenyl)-1,3,4-oxadiazol-2-yl]thio}acetic acid with the metal ions Ni(II), Cu(II), Zn(II), Cd(II) and Sn(II) were prepared in alcoholic medium. The prepared complexes were characterized by FTIR Spectroscopy, electronic spectroscopy 1HNMR, 13CNMR, magnetic susceptibility and conductivity measurements. From the spectral measurements, monomer structures for the complexes were proposed. Square planar geometry was proposed for the copper complex. The other complexes were proposed to be tetrahedral.